`int x/(x-1)^2 dx `

`u= x-1 ==gt x= u+1`

du = dx

`==gt int x/(x-1)^2 dx = int (u+1)/u^2 du`

`= int u/u^2 du+ int 1/u^2 du `

`= int 1/u du + int 1/u^2 du `

`= ln u - 1/u + C = ln (x-1) - 1/(x-1) + C `

`==gt int x/(x-1)^2 dx = ln (x-1) - 1/(x-1) + C`

``

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now